EVALUASI RENCANA KERJA PEMBANGUNAN KENAGARIAN INDERAPURA TENGAH KECAMATAN PANCUNG SOAL KABUPATEN PESISIR SELATAN PROVINSI SUMATRA BARAT - Defrizon Indra; Zulkifli Zulkifli (UIR Press, 2018)
This study aims to determine the level of evaluation plans Kenagarian Work Development in Central Indrapura, where the Development Plan is measured by four indicators, namely: Inputs, Process, Outputs and Outcomes. Type of Research located in Kenagarian Indrapura middle of the District of beheading Problem Pesisir Selatan regency of West Sumatra Province is survey descriptive, namely the priority list of the questionnaire as a data collection tool and data collected by the tool is then used as the main raw material for evaluating the condition of Empirical of objectivity where the destination research at the location studied. There are 3 groups of the population and sample in this research is employees 7, Bamus 5 people, and Society 10. Sampling technique used in data collection is the census technique for employees and Bamus, type and data collection techniques used consist of primary data was collected by using questionnaires and interviews and secondary data was collected using observation. While data analysis technique used is to use tools frequency table. Based on this analysis technique researchers assess and concluded that the Development Plan Evaluation Kenagarian Middle Indrapura districts beheading Problem Pesisir Selatan regency of West Sumatra province are in Interval Good.